The Relationship Between Personal Hygiene Behavior and the Incidence of Vaginal Discharge - Nurlailis Saadah; Fenti Suwarno Putri; Rahayu Sumaningsih; Uswatun Khasanah (International Journal of Advanced Health Science and Technology, 2024)
Adolescence is a transitional period characterized by physical, emotional and psychological changes. Changes in physical aspects are the most important because they take place quickly, drastically and lead to reproductive organs. A person's understanding, attitude, and behavior related to maintaining personal hygiene, beautifying appearance, increasing self-esteem, and preventing disease together can be referred to as personal hygiene behavior. Vaginal discharge is one of the symptoms and signs of infectious diseases in women. The general objective of this study was to determine the relationship between personal hygiene behavior and the incidence of vaginal discharge. The type of research used observational analytic research methods with a cross-sectional approach. The study population was seventh and eighth grade students of SMPN 1 Ngariboyo totaling 179 students. The sampling technique in this study used simple random sampling, obtained a sample size of 124 students. The independent variable is personal hygiene behavior while the dependent variable is vaginal discharge. Data collection using a questionnaire. The results of the gamma correlation test show that there is a relationship between personal hygiene behavior and the incidence of vaginal discharge with a p value of 0.030 (<0.05). It can be concluded that there is a significant relationship between personal hygiene behavior and the incidence of vaginal discharge at SMPN 1 Ngariboyo. It is expected that female students can increase their knowledge in applying personal hygiene behavior towards the incidence of vaginal discharge.